Abundance, Diversity, and Distribution of Primates at Welel Mountain, Kellem Wollega Zone, Oromia Region, Ethiopia - Diriba Fufa; Dereje Yazezew; Gezahegn Degefe; Sibhatu Gebrehiwot (The Scientific World Journal)
Primates are the mammals of the order Primate that is characterized by advanced development of binocular vision and enlargement of the cerebral hemispheres. The aim of this study was to investigate the abundance, diversity, and distribution of primates on Welel Mountain. From August 2017 to February 2018, we collected data from different parts of Welel Mountain during wet and dry seasons of the year and analyzed them using SPSS version 20. We identified four primate species: Chlorocebus aethiops, Cercopithecus mitis, Papio anubis, and Colobus guereza. We conducted t-test analysis for abundance and distribution of primates in wet and dry season of the year, and the P value obtained was 0.20. The mean percentages of primates in forest, woodland, and shrubs were 43.16%, 32.26%, and 24.58%, respectively. Shannon-Wiener diversity index (H′) value was higher in wet season than in dry season. The current study showed that the species are distributed more evenly in wet season than in dry season, and the number of young individuals is more than that of adults. This indicates that currently the status of primates population on Welel Mountain is good. Therefore, to keep the status of primates in the study area effective, wildlife management and conservation policy should be formulated.